2023
DOI: 10.3390/healthcare11243191
|View full text |Cite
|
Sign up to set email alerts
|

Pain Prevalence and Satisfaction with Pain Management in Inpatients: A Cross-Sectional Study

Ángel Becerra-Bolaños,
Annette Armas-Domínguez,
Lucía Valencia
et al.

Abstract: Background: Pain in hospitalized adults is underestimated and undervalued. The aim of this study was to evaluate pain prevalence and satisfaction with the hospital’s pain management among patients attending a tertiary university hospital. Predictor factors of pain were also studied. Methods: A prospective, cross-sectional study was carried out through a structured questionnaire given on one day to all hospitalized patients in a university hospital. Clinical data, such as personal history and analgesic treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
0
1
Order By: Relevance
“…In contrast to a recent report by Becerra-Bolaños et al, which documented an average postoperative pain intensity of 2.7 ± 2.8 on the NRS [ 30 ], our study found higher postoperative pain levels. Several factors might explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to a recent report by Becerra-Bolaños et al, which documented an average postoperative pain intensity of 2.7 ± 2.8 on the NRS [ 30 ], our study found higher postoperative pain levels. Several factors might explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%